The Impact of Nickel Management on Community Socio-Economic Conditions in Morosi District Konawe Regency - Nurlaela; Suharty Roslan; Bakri Yusuf; Muhamad Masri (CV. Literasi Indonesia, 2020)
This study aims to discover the impact of ore nickel management by PT. VDNI (Virtue Dragon Nickel Industry) on the socio-economic conditions of the community in Morosi Village, Morosi District, Konawe Regency. Methodologically, the decision of research informants was used as a purposive sampling technique. The results showed that the impacts of nickel management in Morosi Village included social and economic impacts. Social impacts include increasing education continuity, free health services for workers, making social solidarity between workers, land conflicts between citizens and companies, and decreasing interest in young people to farm. While the impact on the economic condition of the community includes opening up employment opportunities, increasing income, and improving the housing conditions of the workers.